Bio‐inspired proton conducting phytagel derived zwitterionic complex membranes for fuel cells. (6th April 2020) - Karuppasamy, K.; Vikraman, Dhanasekaran; Jang, Kyu‐Won; Ravi, Seenu; Tanveer, Waqas Hassan; Bose, Ranjith; Thandavarayan, Maiyalagan; Kim, Hyun‐Seok
Summary: This study proves synthesis of carbohydrate polymer phytagel based composite proton exchange membranes and employed for their applications in proton exchange membrane fuel cells. Phytagel was sulfonated using chlorosulfonic acid and corresponding composite membranes were prepared by loading different amounts of sulfamic acid (SA) to improve their proton conductivity. Incrementing SA into the sulfonated phytagel substantially boosted the swelling rate to a certain limit without affecting proton conductivity, or thermal and mechanical stabilities. Highest proton conductivity (1.49 × 10 −3  S cm −1 at 353 K) was achieved for 7 wt% SA. Single cell tests on this membrane unveiled an excellent performance at 60°C and 100% relative humidity (RH) compared with the other two membranes. Thus, this study offers may open new possibilities to utilize phytagel based bio‐composite solid polymer electrolytes as proton exchange membranes for fuel cell applications. Abstract : A new type of zwitterionic complex membrane has been successfully synthesized and employed for PEM fuel cell applications. The fabricated phytagel based PEM fuel cell delivered the maximum power and current densities of 93.8 and 225 mA cm −2, respectively.